EFEK MEDIASI KERJASAMA TIM DALAM HUBUNGAN ANTARA GAYA KEPEMIMPINAN DAN KINERJA PROYEK - Hotono, Shintia; Sintaasih, Desak Ketut; Subudi, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The leader is indispensable in achieving project success. The leader must be able to adjust leadership style that is suitable to be applied to specific situations and the follower. The purpose of this study was to determine the relationship between leadership styles, team work as a mediating role in the performance of the project. The population in this study were all employees of the project. Location of research at PT. Ciputra Property Tbk - Sub Holding 3A - Bali, Jakarta and Semarang. Sampling technique using saturated sample so that the same population with the sample. Total respondents 121 employees. The research instrument used questionnaires and data analysis techniques using PLS. The results showed that transformational and transactional leadership style to teamwork influence positively, transformational leadership style to project performance affected positively whereas transactional leadership style to project performance is not influential in running the project and also teamwork as mediation does not affect the project performance.
Keywords: transformational leadership, transactional leadership style, teamwork and project performance